Intra‐amniotic digoxin for feticide between 21 and 30 weeks of gestation: a prospective study. (12th March 2019) - Sharvit, M; Klein, Z; Silber, M; Pomeranz, M; Agizim, R; Schonman, R; Fishman, A
Abstract : Objective: Intra‐amniotic injection of digoxin is a well‐known method for feticide before inducing a termination of pregnancy (TOP) at 17–24 weeks of gestation. Information on its effectiveness when administered after 24 weeks of gestation is limited. This study evaluated the efficacy of intra‐amniotic digoxin injection for inducing fetal demise within 18–24 hours, at 21–30 weeks of gestation, and its safety. Design: Prospective cohort study. Setting: Tertiary university medical centre. Population: Women at 21–30 weeks of gestation with a singleton pregnancy, admitted for TOP. Methods: Intra‐amniotic injection of 2 mg of digoxin was performed 1 day before medical TOP. Fetal heart activity was evaluated by ultrasound for 18–24 hours after the injection. Serum digoxin level and maternal electrocardiogram (ECG) were evaluated 6, 10, and 20 hours after injection. Main outcome measure: Frequency of successful fetal demise. Results: Fifty‐nine women participated in the study. The mean gestational age was 24 +2  weeks (range 21 +0 –30 +0 ), with 29 (49.2%) beyond 24 +0  weeks of gestation. Fetal cardiac activity arrest was achieved in 55/59 cases (93.2%). Normal maternal ECG recordings were noted in all cases. Mean serum digoxin levels 6 and 10 hours after injection were in the therapeutic range (1.3 ± 0.7 ng/l and 1.24 ± 0.49 ng/l, respectively) and below the toxic level (2 ng/l). Extramural delivery following digoxin did not occur. There were no cases of chorioamnionitis. Conclusion: Intra‐amniotic digoxin for feticide at 21–30 weeks of gestation in a singleton pregnancy appears effective and safe before TOP at advanced gestational ages. Tweetable abstract: This study shows that feticide by intra‐amniotic digoxin injection at 21–30 weeks of gestation appears effective and safe. Tweetable abstract: This study shows that feticide by intra‐amniotic digoxin injection at 21–30 weeks of gestation appears effective and safe.